Global Journalism Ethics - STEPHEN J.A. WARD (McGill-Queen's University Press, 2010)
Journalism faces a crisis of ethics that threatens to lower its standards, demean its honorable history, and question its future as a democratic agent of the public sphere. Economic and social forces undermine the relevancy of journalism principles while technology creates a universe of new media that redefines the definition of journalist. These staggering changes occur as news organizations can now, more easily than ever before, reach people around the world. Journalists struggle to maintain a credible ethical identity as they sail the roiling sea of wired and wireless media, a postmodern version of Heraclitusâ€™s world of flux where nothing can be known because nothing stays the same. What can ethics mean for a profession that must provide instant news and analysis, and where everyone can be a publisher, thanks to the internet? Rapid change has created confusion about existing goals and standards of journalism. This confusion runs deep, going even deeper than debates about specific problems of practice, such as the use of confidential sources. The confusion extends to how journalists should serve the public good and what journalists are â€œfor.â€1 No wonder the ship of journalism lacks direction.